Canada Goose Management Series: Modify Human Behavior - Drake, David (Rutgers New Jersey Agricultural Experiment Station, Rutgers Cooperative Extension, 2004)
There is a wide range of non-lethal and lethal options available for Canada goose ( Branta canadensis ) management. This fact sheet, part of a series that examines goose management options currently employed, will present information on modifying human behavior to deter geese from visiting your property. We will define the technique and explore the advantages and disadvantages of modifying human behavior in terms of, among other factors, amount of effort required to implement, effectiveness, and cost. Fact Sheet FS1028 Purpose: To provide information about managing Canadian geese by modifying human behavior